A Study of Problems and Prospects of Sericulture in Shivamogga District, Karnataka - Sarala, K. S.; Aravinda, K. N. (Indian Journal of Marketing, 2010)
Sericulture is one of the labour intensive cottage industries involving mulberry cultivation, silkworm rearing and egg production, reeling and weaving of the loom and other post cocoon processes like twisting, dyeing, painting, finishing etc. along with the utilization of by products, offering a most promising alternative agricultural activity. Sericulture is a way of life in India. Sericulture promotes self-employment and other livelihood activities in the rural economy and helps to accelerate income and provides employment opportunities to 35 million people and is practiced in Karnataka, Andhra Pradesh, Tamil Nadu, Jammu & Kashmir and West Bengal (Mulberry Silk) Jharkhand, Orissa, Chhattisgarh and North-Eastern States (Non-Mulberry Silk). There are number of problems in Sericulture in Shimoga district i.e., labour, financial, marketing etc. The reviews of the published work also reveals the fact that no work of worth consideration on the topic of the present study has been undertaken by the researchers in the past. Hence, there is need for present study to fill the research gap that exists at present. In order to cover this gap, the present research was undertaken.